Rapid method for identification of transgenic fish zygosity - Alimuddin, .; Yoshizaki, G.; Carman, O. (Jurnal Akuakultur Indonesia, 2007)
Identification of zygosity in transgenik fish is normally achieved by PCR analysis with genomic DNA template extracted from the tissue of progenies which are derived by mating the transgenic fish and wild-type counterpart.  This method needs relatively large amounts of fish material and is time- and labor-intensive. New approaches addressing this problem could be of great help for fish biotechnologists.  In this experiment, we applied a quantitative real-time PCR (qr-PCR) method to analyze zygosity in a stable line of transgenic zebrafish (Danio rerio) carrying masu salmon, Oncorhynchus masou D6-desaturase-like gene. The qr-PCR was performed using iQ SYBR Green Supermix in the iCycler iQ Real-time PCR Detection System (Bio-Rad Laboratories, USA).  Data were analyzed using the comparative cycle threshold method.  The results demonstrated a clear-cut identification of all transgenic fish (n=20) classified as a homozygous or heterozygous.  Mating of those fish with wild-type had revealed transgene transmission to the offspring following expected Mendelian laws. Thus, we found that the qTR-PCR to be effective for a rapid and precise determination of zygosity in transgenic fish. This technique could be useful in the establishment of breeding programs for mass transgenic fish production and in experiments in which zygosity effect could have a functional impact. Keywords: quantitative real-time PCR; zygosity; transgenic fish; mass production   ABSTRAK Identifikasi sigositas ikan transgenik biasanya dilakukan menggunakan analisa PCR dengan cetakan DNA genomik yang diekstraksi dari jaringan ikan hasil persilangan antara ikan transgenik dan ikan normal.   Metode ini memerlukan ikan dalam jumlah yang banyak, dan juga waktu serta tenaga.  Pendekatan baru untuk mengatasi masalah tersebut akan memberikan manfaat besar kepada peneliti bioteknologi perikanan.  Pada penelitian ini, kami menggunakan metode PCR real-time kuantitatif (krt-PCR) untuk menganalisa sigositas pada satu strain ikan zebra (Danio rerio) transgenik yang membawa gen D6-desaturase-like dari ikan salmon masu, Oncorhynchus masou.  krt-PCR dilakukan menggunakan iQ SYBR Green Supermix pada mesin iCycler iQ Real-time PCR Detection system (Bio-Rad Laboratories, USA).  Data dianalisis menggunakan metode pembandingan nilai cycle threshold.  Hasil penelitian menunjukkan bahwa semua ikan transgenik (n=20) yang diidentifikasi dapat diklasifikasikan secara jelas sebagai ikan homosigot atau heterosigot.  Persilangan antara ikan transgenik tersebut dengan ikan normal menunjukkan transmisi transgen ke keturunannya mengikuti hukum segregasi Mendel.  Dengan demikian, metode krt-PCR adalah efektif untuk penentuan sigositas secara cepat dan tepat pada ikan transgenik.  Teknik ini dapat berguna dalam program produksi ikan transgenik secara massal dan dalam percobaan dimana faktor sigositas memberikan pengaruh nyata. Kata kunci: kuantitatif real-time PCR; sigositas, ikan transgenik; produksi massal